The Effect of Long Term Thermal Exposure on Plastics and Elastomers - McKeen, Laurence W., author 519968; ScienceDirect (Online service) 7722 (Kidlington : William Andrew, 2021)
The Effect of Long Term Thermal Exposure on Plastics and Elastomers, Second Edition brings together a wide range of essential data on the effect of long-term thermal exposure on plastics and elastomers, enabling engineers to make optimal material choices and design decisions. This second edition has been thoroughly revised to include the latest data and materials. This highly valuable handbook will support engineers, product designers, R&D professionals, and scientists who are working on plastics products or parts for high temperature environments across a range of industries.